Molecular identification and antifungal susceptibility testing of Aspergillus species among patients with chronic pulmonary aspergillosis in Nigeria - Adeyinka A. Davies; Bram Spruijtenburg; Eelco F.J. Meijer; Iriagbonse I. Osaigbovo; Oluwaseyi Balogun; Abiola Adekoya; Titilola Gbaja-Biamila; Jacques F. Meis; Rita Oladele (African Journal of Laboratory Medicine)
Background: Triazole resistance in Aspergillus spp. has therapeutic implications for managing chronic pulmonary aspergillosis (CPA) worldwide. However, antifungal susceptibility testing (AFST) is not routinely performed in Nigeria, a country with a high CPA burden.